2019
DOI: 10.1016/j.ygcen.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gonadotropin-releasing hormone system in the Neotropical teleost, Steindachneridion parahybae during the annual reproductive cycle in captivity

Abstract: This study evaluated by immunohistochemical and Western blot methods, the distribution of two distinct gonadotropin-releasing hormones (GnRHs), corresponding to catfish GnRH (cfGnRH or GnRH1) and chicken-II GnRH (cGnRH-II or GnRH2), in Steindachneridion parahybae females in captivity, focusing these analyses on the reproductive cycle by semi-quantification of optical density (OD). Further, we found that the GnRH neuronal systems co-localized with their respective GnRH-associated peptides (GAPs). A group of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 74 publications
2
20
0
3
Order By: Relevance
“…S. parahybae presents two different gonadotropin‐releasing hormone (GnRH) forms (GnRH1 and GnRH2). GnRH1 neurons and fibres are intimately related to pituitary regulation, and GnRH2 neurons and fibres (which do not innervate the pituitary gland) are probably related to neuromodulation and/or reproductive behaviour in this species (Honji et al ., 2019). Vitellogenesis is likely to be controlled by follicle‐stimulating hormone, and during the RC in S. parahybae , the data found here (E 2 plasma profile) and this species' gonadotropin profile (Honji et al ., 2015) suggested a higher amount of this hormone during the PRV, displaying a close relationship with the seasonality of ovarian development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. parahybae presents two different gonadotropin‐releasing hormone (GnRH) forms (GnRH1 and GnRH2). GnRH1 neurons and fibres are intimately related to pituitary regulation, and GnRH2 neurons and fibres (which do not innervate the pituitary gland) are probably related to neuromodulation and/or reproductive behaviour in this species (Honji et al ., 2019). Vitellogenesis is likely to be controlled by follicle‐stimulating hormone, and during the RC in S. parahybae , the data found here (E 2 plasma profile) and this species' gonadotropin profile (Honji et al ., 2015) suggested a higher amount of this hormone during the PRV, displaying a close relationship with the seasonality of ovarian development.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were randomly divided into two ponds (200 m 2 ) to characterize the annual RC. During this period, carnivorous fish were fed at 08.00 and 16.00 hours with commercial extruded food containing 40% crude protein at a rate of 2% biomass per day, provided twice a day and under natural photoperiod, according to previous studies (Honji et al ., 2012, 2015, 2017, 2019). In addition, water quality parameters (temperature and dissolved oxygen) were monitored daily using an oximeter (Horiba – ModU10) and are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ministry, 2018). The catfish species are widely cultivated for the provision of animal protein-based feed (Jooste et al, 2015;Kusuma et al, 2015;Fisheries Research Institute of Indonesia, 2018). This fish species has a high growth rate and adaptable to environmental factors, such as temperature and oxygen changes.…”
Section: Clarias Gariepinusmentioning
confidence: 99%
“…In C. gariepinus broodstock, the hypothalamic-pituitary-gonad axis primarily manages the reproduction activity. The GnRH is a key player for reproductive activity (Chaube et al, 2015;Golan et al, 2015;Honji et al, 2019). When C. gariepinus broodstock spawn, the gonads are influenced by the hypothalamus, as it synthesizes and liberates the GnRH, stimulates the anterior pituitary to produce the gonadotropin hormone; gonadotropins stimulate steroidogenesis (Zohar et al, 2010;Borella et al, 2020).…”
Section: Clarias Gariepinusmentioning
confidence: 99%
“…These studies are generally descriptive or comparative in nature, relating reproductive characteristics to biotic and abiotic variables, and thereby presenting an ecological perspective. In aquacultural environments, several studies have been conducted in purpose to describe the gametogenesis and also the reproductive cycle of neotropical species, either complete as in lambaris (Chehade et al, 2015;Mazzoni et al, 2015;Cassel et al 2017) and Rhamdia quelen (Ghiraldelli et al, 2008;Mazzoni et al, 2020) or partial as in the studies with Steindachneridion parahybae (Honji et al, 2019), Prochilodus lineatus (De Souza et al, 2015) and Colossoma macropomum (Pires et al, 2017). Studies on this topic with species of Bryconidae from captivity are rare and those found, both with matrinxã, Brycon cephalus (Romagosa et al, 2000) and Brycon amazonicus (Arias et al, 2006).…”
Section: Introductionmentioning
confidence: 99%